2022
DOI: 10.3390/molecules27072233
|View full text |Cite
|
Sign up to set email alerts
|

Concise Syntheses of Marine (Bis)indole Alkaloids Meridianin C, D, F, and G and Scalaridine A via One-Pot Masuda Borylation-Suzuki Coupling Sequence

Abstract: N-Protected 3-iodoindoles were reacted with (di)azine halides in a sequentially Pd-catalyzed one-pot fashion, i.e., by Masuda borylation–Suzuki coupling (MBSC) sequence. This methodology was successfully applied to the concise syntheses of marine indole alkaloids meridianin C, D, F, and G, as well as to the bisindole alkaloid scalaridine A, which were obtained in moderate to excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The additional deprotecting step does not influence the overall yields. The synthesized examples have been isolated with yields ranging from 25 to 80% [ 63 , 64 ].…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The additional deprotecting step does not influence the overall yields. The synthesized examples have been isolated with yields ranging from 25 to 80% [ 63 , 64 ].…”
Section: Synthesismentioning
confidence: 99%
“…The Müller group could show the versatility of the MBSC sequence by transferring their meridianin protocol to the synthesis of meriolins and other biaryl systems [ 18 , 63 , 64 , 71 ]. In a one-pot-process, 7-azaindoles 99 were transformed to the corresponding pinacolyl boronic acid esters in a palladium-mediated Masuda borylation.…”
Section: Synthesismentioning
confidence: 99%
“…To date, several synthetic methods of meridianin analogues have been reported. Among them, there are mainly five widely used synthetic strategies: application of the Bredereck protocol [65,66], cross-coupling [67][68][69], conversion of 3-cyanoacetyl indole [9,70], alkenylation and condensation reaction of indoles [71] and indolization of nitro-soarenes [72].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Jiang et al [67] and Müller et al [69] separately reported a palladium catalyzed crosscoupling reaction of 3-indolylboronic and pyrimidine moieties to prepare meridianin analogues. Jiang's protocol was a traditional Suzuki coupling reaction between indolyboronic acid and chloroaminopyrimidine.…”
Section: Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation